The Little Exercise Book of Advertising, vol. 1 - LEPĂDATU, Ioana; SZAMBOLICS, Julia (2024)
The Little Exercise Book of Advertising offers theoreticalconcepts and practical exercises that students can use intheir classes. Each chapter ends with creatively designedexercises that highlight that chapter's specific theory. Thisbook includes tasks such as developing a buyer personaprofile, formulating a creative brief, comprehending a mediastrategy, and understanding the importance of correctbudgeting.